2009
DOI: 10.1177/0748233709106624
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin attenuates benzo[α] pyrene-induced testicular toxicity in rats via regulation of oxidant/antioxidant balance

Abstract: Benzo[alpha]pyrene (BaP) is one of the polycyclic aromatic hydrocarbons, which has shown carcinogenic, teratogenic, and mutagenic potentials. The reproductive toxicity of BaP in male was not well investigated. Thereby, we have addressed in the current study the testicular toxicity of BaP and the postulate whether or not the citrus flavonoid, hesperidin (HDN), could ameliorate such toxicity in male Swiss albino rats. In this sense, animals were challenged with BaP (50 mg/kg/day, orally) for 10 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…Other oxidative stress associated proteins like serotransferrin, ECE-2, retinoid binding protein, endoplasmin, hemopexin and ALDH2 were also associated with Bap and DBP exposure (Klipper et al, 2010). Suggesting that the exposure of Bap and DBP may disturb the oxidant/antioxidant balance and active the cAMP signal pathway in germ cells (Arafa et al, 2009;Mayati et al, 2012). Mitofilin, endoplasmin and MST4 are also associated with apoptotic process.…”
Section: The Changes In Total Protein Expressionmentioning
confidence: 93%
“…Other oxidative stress associated proteins like serotransferrin, ECE-2, retinoid binding protein, endoplasmin, hemopexin and ALDH2 were also associated with Bap and DBP exposure (Klipper et al, 2010). Suggesting that the exposure of Bap and DBP may disturb the oxidant/antioxidant balance and active the cAMP signal pathway in germ cells (Arafa et al, 2009;Mayati et al, 2012). Mitofilin, endoplasmin and MST4 are also associated with apoptotic process.…”
Section: The Changes In Total Protein Expressionmentioning
confidence: 93%
“…Doses as low as 1 mg/kg bw per day for 90-day exposures (Zheng et al, 2010) were effective in perturbing reproductive parameters. Major effects include impaired fertility in exposed adults (Arafa et al, 2009; Chen et al, 2011; Xu et al, 2010; Zheng et al, 2010) and developing rodents (Kristensen et al, 1995; Mackenzie and Angevine, 1981; Nakamura et al, 2012), which appears to be mediated by an AHR-dependent MOA (Neal et al, 2010; Sadeu and Foster, 2011). Overall, it is apparent that BaP affects the reproductive fitness of exposed organisms by impacting germ cell quality and quantity, hormone balance and gonadal tissue growth and development at exposure doses as low as 1 mg/kg bw per day in rodents (LOAEL).…”
Section: Traditional Risk Assessment Approach (Ra1)mentioning
confidence: 99%
“…Hesperidin also showed antiproliferative effect in MCF-7 cells transfected with green fluoresens protein (GFP)/alpha-tubulin (MCF-7-GFP-Tubulin) (Lee et al, 2009). It is also reported that hesperidin protective effect in benzo [a]pirene induced testicular toxicity paradigm and repaired the function of lactate dehydrogenase (LDH-X), superoxide dismutase (SOD), dan glutathione-Stransferase (GST) enzyme (Arafa et al, 2009). Previous study has reported that Hesperidin could induce apoptosis in human colon cancer cells through CASP3 activation.…”
Section: Introductionmentioning
confidence: 97%